Sunflower Production in North Central and Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1995)
This publication describes the cost-return projections for producing sunflowers in north central and northeastern Kansas.
MF2144_1995_10
Keywords: MF2144; Crops; Economics; MF